Historical perspectives on Mexican transnationalism: with notes from Angumacutiro - Weber, Devra (Social justice, 1999)
Part of a special issue on collective identities, social problems, and movements. The writer examines historical perspectives on Mexican transnationalism. She highlights the fact that transnational migration is not a new phenomenon and that, in fact, it has existed longer than the concept of the “nation.” She discusses historical interlinkages between Mexicans on both sides of the U.S. border, drawing on oral histories from Angumacutiro, Michoacán, Mexico. She argues that the term “transnational” is problematic because it fuses an economic process with human migration, and she predicts that it will become obsolete. She concludes that the meanings and analysis of the history and experience of migrants themselves will provide more insight into the past, present, and future of migration.